Relationship Between Number of Vibrio sp in Sediment and in Blood Cockle (Anadara granosa) in the Coastal Waters of Bina Maju Village Kepulauan Meranti District - Yahya Benardus Sihombing; Nursyirwani '; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aimed to find relationship between numbers of Vibrio sp in sediment and in blood cockle. This research was conducted from March until May 2017. Survey method was used in this research. The data was analyzed descriptively and statistically using simple linear regression. The highest average log number of Vibrio sp in sediment was find at sampling point 2 (7.9033 CFU/g) and the lowest was at sampling point 4 (7.3187 CFU/g). Meanwhile in blood cockle the highest Vibrio number was at sampling point 3 (7.6889 CFU/g) and the lowest was at sampling point 1 (6.3411 CFU/g). Simple linear regression indicated the r value (correlation coefficient) was 0.31, showed was low which meant that the relationship between number of Vibrio sp in sediment and in blood cockle.Key words: Relationship, Vibrio sp, Sediment, Blood Cockle, Coastal waters